Fatigue and Fracture Reliability Engineering - Xiong, J.J.; Shenoi, R.A.; SpringerLink (Online service) (London : Springer London, 2011)
Fatigue and Fracture Reliability Engineering is an attempt to present an integrated and unified approach to reliability determination of fatigue and fracture behaviour, incorporating probability, statistics and other related areas. A series of original and practical approaches, are suggested in Fatigue and Fracture Reliability Engineering, including new techniques in determining fatigue and fracture performances. It also carries out an investigation into static and fatigue properties, and into the failure mechanisms of unnotched and notched CFR composite laminates with different lay-ups to optimize the stacking sequence effect. Further benefits include: a novel convergence-divergence counting procedure to extract all load cycles from a load history of divergence-convergence waves; practical scatter factor formulae to determine the safe fatigue crack initiation and propagation lives from the results of a single full-scale test of a complete structure; and a nonlinear differential kinetic model for describing the dynamical behaviour of an atom at a fatigue crack tip. Fatigue and Fracture Reliability Engineering is intended for practising engineers in marine, civil construction, aerospace, offshore, automotive and chemical industries. It is also useful reading for researchers on doctoral programmes, and is appropriate for advanced undergraduate and postgraduate programmes in any mechanically-oriented engineering discipline.
1. Deterministic Theorem on Fatigue and Fracture -- 2. Reliability and Confidence Levels of Fatigue Life -- 3. Principles Underpinning Reliability based Prediction of Fatigue and Fracture Behaviours -- 4. Data Treatment and Generation of Fatigue Load Spectrum -- 5. Reliability Design and Assessment for Total Structural Life -- 6. Reliability Prediction for Fatigue Damage and Residual Life in Composites -- 7. Chaotic Fatigue.
Keywords: ENGINEERING; ENGINEERING DESIGN; SYSTEM SAFETY; MATERIALS; ENGINEERING; QUALITY CONTROL, RELIABILITY, SAFETY AND RISK; STATISTICS FOR ENGINEERING, PHYSICS, COMPUTER SCIENCE, CHEMISTRY AND EARTH SCIENCES; METALLIC MATERIALS; MACHINERY AND MACHINE ELEMENTS; ENGINEERING DESIGN